Asthma in Hispanics. An 8-Year Update - Rosser, Franziska J. (American Thoracic Society, 2014)
This review provides an update on asthma in Hispanics, a diverse group tracing their ancestry to countries previously under Spanish rule. A marked variability in the prevalence and morbidity from asthma remains among Hispanic subgroups in the United States and Hispanic America. In the United States, Puerto Ricans and Mexican Americans have high and low burdens of asthma, respectively (the “Hispanic Paradox”). This wide divergence in asthma morbidity among Hispanic subgroups is multifactorial, likely reflecting the effects of known (secondhand tobacco smoke, air pollution, psychosocial stress, obesity, inadequate treatment) and potential (genetic variants, urbanization, vitamin D insufficiency, and eradication of parasitic infections) risk factors. Barriers to adequate asthma management in Hispanics include economic and educational disadvantages, lack of health insurance, and no access to or poor adherence with controller medications such as inhaled corticosteroids. Although considerable progress has been made in our understanding of asthma in Hispanic subgroups, many questions remain. Studies of asthma in Hispanic America should focus on environmental or lifestyle factors that are more relevant to asthma in this region (e.g., urbanization, air pollution, parasitism, and stress). In the United States, research studies should focus on risk factors that are known to or may diverge among Hispanic subgroups, including but not limited to epigenetic variation, prematurity, vitamin D level, diet, and stress. Clinical trials of culturally appropriate interventions that address multiple aspects of asthma management in Hispanic subgroups should be prioritized for funding. Ensuring high-quality healthcare for all remains a pillar of eliminating asthma disparities.